2018
DOI: 10.1021/acs.analchem.7b04854
|View full text |Cite
|
Sign up to set email alerts
|

Conformational μ-Conotoxin PIIIA Isomers Revisited: Impact of Cysteine Pairing on Disulfide-Bond Assignment and Structure Elucidation

Abstract: Peptides and proteins carrying high numbers of cysteines can adopt various 3D structures depending on their disulfide connectivities. The unambiguous verification of such conformational isomers with more than two disulfide bonds is extremely challenging, and experimental strategies for their unequivocal structural analysis are largely lacking. We synthesized all 15 possible isomers of the 22mer conopeptide μ-PIIIA and applied 2D NMR spectroscopy and MS/MS for the elucidation of its structure. This study provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 47 publications
5
54
0
Order By: Relevance
“…The pharmacological potential to modulate or block the ion channel activity and their synthetic availability make conotoxins promising candidates for new analgesics. However, Heimer et al recently showed on the example of µ-PIIIA (three disulfide bonds) the complexity of the synthesis, purification, and analytical characterization of one specific isomer in the multitude of different potentially formed disulfide-bridged isomers of those cysteine-rich peptides (Heimer et al, 2018). With respect to this, ionic liquids have proven to be a promising solvent for controlling the oxidative folding process (Miloslavina et al, 2010).…”
Section: Conotoxins and Granulinsmentioning
confidence: 99%
“…The pharmacological potential to modulate or block the ion channel activity and their synthetic availability make conotoxins promising candidates for new analgesics. However, Heimer et al recently showed on the example of µ-PIIIA (three disulfide bonds) the complexity of the synthesis, purification, and analytical characterization of one specific isomer in the multitude of different potentially formed disulfide-bridged isomers of those cysteine-rich peptides (Heimer et al, 2018). With respect to this, ionic liquids have proven to be a promising solvent for controlling the oxidative folding process (Miloslavina et al, 2010).…”
Section: Conotoxins and Granulinsmentioning
confidence: 99%
“…1) contain cysteine residues, which may be present in the oxidized form in the protein. In order to clarify the oxidation state of these cysteines, we incubated hemopexin with the alkylating agent 2-iodoacetamide and performed mass spectrometry measurements 35 . This analysis revealed that all cysteines are oxidized in wild-type hemopexin, which was also confirmed by a negative result from the Ellman’s test for free thiols 35 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to clarify the oxidation state of these cysteines, we incubated hemopexin with the alkylating agent 2-iodoacetamide and performed mass spectrometry measurements 35 . This analysis revealed that all cysteines are oxidized in wild-type hemopexin, which was also confirmed by a negative result from the Ellman’s test for free thiols 35 . Thus, peptide H150 was synthesized with an intramolecular disulfide bond and in all other peptides, disulfide bonds were mimicked by insertion of a methylated cysteine during synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations